2018
DOI: 10.3390/molecules23112770
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Constituents of Lamium album L. as Inhibitors of Cytokine Secretion in Human Neutrophils

Abstract: The traditional role of Lamium album L. (white dead nettle, Lamiaceae) in providing relief from pain in rheumatism as well as vaginal and cervical inflammation was described. The aim of the study was to screen for the anti-inflammatory bioactivity of compounds isolated from aqueous-methanolic extract of Lamium album herb in human neutrophils (PMNs). The effect of the compounds on the inhibition of selected inflammatory markers released by neutrophils, such as cytokines (IL-8, TNF-α), was studied. The molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Despite singular exceptions (e.g., martynoside from the class of phenylpropanoids has been identified in Salvia officinalis), it was even concluded that phenylpropanoids might be considered the chemotaxonomic markers differentiating these two subfamilies [30]. In our previous study, we identified few phenylpropanoids including verbascoside (6), lamiusides A, B, D, and E in the herb of L. album [16,17]. According to previous data phenylpropanoids, such as verbascoside (6) and isoverbascoside, may reach up to 55% of the total phenolic content in a SPE-purified ethanolic extract [21].…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Despite singular exceptions (e.g., martynoside from the class of phenylpropanoids has been identified in Salvia officinalis), it was even concluded that phenylpropanoids might be considered the chemotaxonomic markers differentiating these two subfamilies [30]. In our previous study, we identified few phenylpropanoids including verbascoside (6), lamiusides A, B, D, and E in the herb of L. album [16,17]. According to previous data phenylpropanoids, such as verbascoside (6) and isoverbascoside, may reach up to 55% of the total phenolic content in a SPE-purified ethanolic extract [21].…”
Section: Resultsmentioning
confidence: 94%
“…In addition, it plays a role in a phylogenetic recognition and differentiation within Lamium genus [19], and its biological significance has been preliminary proved [16]. In addition to the interleukin 8 (IL-8) and tumor necrosis factor α (TNF-α) inhibitory activity in human neutrophils, lamalbid (1) has been reported to inhibit reactive oxygen species production and scavenge 2,2-diphenyl-1-picrylhydrazyl radical (66.56%) at a concentration of 100 µg mL −1 [16,32]. For this reason, the quantitation of lamalbid (1) might be also included in the assessment of Lamii albi flos quality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations